2019
DOI: 10.1016/j.tmrv.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Chimeric Antigen Receptor T-Cell (CAR-T) Therapy in Cancer: A Systematic Review and Meta-Analysis

Abstract: Promising efficacy results of chimeric antigen receptor (CAR) T-cell therapy have been tempered by safety considerations. Our objective was to comprehensively summarize the efficacy and safety of CAR-T cell therapy in patients with relapsed or refractory hematologic or solid malignancies. MEDLINE, Embase, and the Cochrane Register of Controlled Trials (inception -November 21, 2017). Interventional studies investigating CAR-T cell therapy in patients with malignancies were included. Our primary outcome of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 78 publications
3
122
1
Order By: Relevance
“…Our patient partners identi ed quality of life and health utility measures as important outcomes to patients. We found that of the 60 clinical trials identi ed by our systematic review, none reported these outcome measures (12). Though we were unable to extract data for these outcomes, our nding points to the need for CAR-T cell therapy clinical trials to consult with patients during protocol development so that such outcomes can be measured and reported.…”
Section: Systematic Reviewmentioning
confidence: 85%
See 2 more Smart Citations
“…Our patient partners identi ed quality of life and health utility measures as important outcomes to patients. We found that of the 60 clinical trials identi ed by our systematic review, none reported these outcome measures (12). Though we were unable to extract data for these outcomes, our nding points to the need for CAR-T cell therapy clinical trials to consult with patients during protocol development so that such outcomes can be measured and reported.…”
Section: Systematic Reviewmentioning
confidence: 85%
“…Chimeric Antigen Receptor (CAR) T-cell therapy, is a promising new class of personalized treatment for blood cancers, where some of a patient's own T-cells are removed, genetically modi ed in a laboratory to enable the them to speci cally target and kill cancer cells, then re-administered to the patient. Despite CAR-T therapy's promising initial results for CD19 positive blood cancers (12), further work remains to con rm both the safety and e cacy of speci c, novel CAR-T therapy products. Our team is thus conducting the rst Canadian-led, early phase clinical trial to assess the safety and effectiveness of a novel CAR-T treatment for resistant blood cancer (Trial Name: Canadian-Led Immunotherapy in Cancer Trial-01 (CLIC-01); clinicaltrials.gov registration #NCT03765177).…”
Section: The Getting Better Outcomes With Chimeric Antigen Receptor Tmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Among all haematologic malignancies, ALL has shown the highest response to anti-CD19 CAR-T cells with a complete response rate of 77%, as shown in a recently published meta-analysis. 8 Anti-CD19 CAR-T cells are genetically engineered T cells that express a surface single-chain immunoglobulin fragment targeting CD19 antigen found on malignant B cells. 9 The manufacturing and distribution of such therapy is complex, requiring sophisticated technology and rigorously regulated processes.…”
mentioning
confidence: 99%
“…We identi ed several systematic reviews focused on safety and e cacy of CD19 CAR T-cell therapies (20)(21)(22). Furthermore, Grigor et al and Yu et al conducted systematic reviews of all CAR T-cell therapies (23,5). These reviews only included studies up to late 2017 and early 2018, respectively, and both studies excluded conference abstracts.…”
mentioning
confidence: 99%